Education Management, Education Theory and Education Application - Wang, Yuanzhi (Advances in Intelligent and Soft Computing, 2012)
This volume includes extended and revised versions of a set of selected papers from the 2011 2nd International Conference on Education and Educational Technology (EET 2011) held in Chengdu, China, October 1-2, 2011. The mission of EET 2011 Volume 2 is to provide a forum for researchers, educators, engineers, and government officials involved in the general areas of education management, education theory and education application to disseminate their latest research results and exchange views on the future research directions of these fields. 133 related topic papers were selected into this volume. All the papers were reviewed by 2 program committee members and selected by the volume editor Prof. Yuanzhi Wang, from Intelligent Information Technology Application Research Association, Hong Kong. The conference will bring together leading researchers, engineers and scientists in the domain of interest. We hope every participant can have a good opportunity to exchange their research ideas and results and to discuss the state of the art in the areas of the education management, education theory and education application.